Study on a new mechanism of sterilization in imposex affected females of tropical marine neogastropod, Thais sp. - Mohamat Yusuff, Ferdaus; Zulkifli, Syaizwan Zahmir; Otake, Tsuuguo; Harino, Hiroya; Ismail, Ahmad (Triveni Enterprises, 2014)
The morphological expressions and histopathological analysis of the gonads of a tropical marine neogastropod species (Thais sp.) from East Malaysia revealed new evidence of mechanical sterility in the imposex affected females. The gradual development of imposex was classified into five stages (Stage 0 to Stage 4) with three types of sterility conditions; Type A caused prohibition of copulation and capsule formation; Type B prohibits the releasing process of eggs; and gonads in Type C are infertile.? Further analysis is needed to confirm, if the gonad malformation in imposex affected snails is generated specifically by tributyltin (TBT) or by other possible factors. The levels of imposex incidence (stages and percentages) were greater in a marina and decreased with increasing distance from the marina. Organotin tissue burden across the sexes showed that dibutyltin (DBT) as well as TBT might be the elements inducing imposex in Thais sp. from Miri in East Malaysia.